Scientific Knowledge Integration and Overlapping Methodological Mechanisms in the Arab-Islamic Culture Analytical- Explanatory Study.: Integrasi Pengetahuan Ilmiah dan Tumpang Tindih Mekanisme Metodologis dalam Budaya Arab-Islam: Kajian Analitis-Eksplanatori - Moussaoui, Ismail (ELOQUENCE : Journal of Foreign Language, 2024)
Background: The research starts from the issue of specialization and its consequences, which led to the fragmentation of sciences, causing humans to lose a holistic cognitive view of various aspects of religious and worldly life. This contrasts with the perspective of ancient Muslim scholars and their deep understanding of existence, as they possessed integrated scientific mechanisms during a time when the cognitive sciences were interconnected, overlapping, and linked to the Quranic text. Purpose This paper aims to explore the concept of knowledge integration and its scientific mechanisms within Arab-Islamic culture. It highlights the contributions of Muslim scholars in establishing this concept and its role in advancing scientific progress across ages, linking it to the Quran. The study focuses on the interconnection of knowledge and sciences, their integration in serving and studying the Quran through an objective scientific approach grounded in transmitted, rational, and linguistic science. Method: he research is based on two methodologies: the integrative approach in presenting research knowledge according to a functional interpretive pattern of a series of progressive and interconnected scientific concepts that cover various topics related to the sciences of language, doctrinal sciences, and rational sciences among Muslim scholars, without dividing knowledge into separate fields. The second methodology is the analytical approach, which analyzes the issue of cognitive specialization and highlights its shortcomings in contrast to the integrative and holistic knowledge found among Muslim scholars. Results and Discussion: The research results revealed a scientific overlap between linguistic, religious, and philosophical mechanisms, demonstrating a mutual benefit and exchange between the sciences, both in content and form. This integration is one of the key factors in the development, advancement, and semantic flourishing of sciences, free from intellectual conflict, serving humanity and facilitating both its religious and worldly affairs. Conclusions and Implications: The integration of knowledge across sciences has sparked the curiosity of scholars and those interested in science and knowledge, as they found in these fields a source of fascination that strengthens their passion for science and love of learning. The study also recommends conducting new integrative studies between transmitted and rational sciences in the study of Quranic miracles and their application to reality.